Corporate Governance, Profitability, and Financial Statement Fraud Risk in Indonesian Pharmaceutical Companies - Dela Zati Sapitri; Fitri Mareta; Depita Anggraini (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
This study examines the effects of independent commissioners, managerial ownership, and audit committee size on financial statement fraud risk and tests whether profitability moderates those relationships in Indonesian pharmaceutical companies. The study addresses a sector-specific evidence gap by examining all three governance mechanisms and the profitability interaction in a narrowly defined, highly regulated setting. Secondary annual-report data from 2020–2024 were selected purposively. Ten companies yielded 50 initial firm-year observations, four casewise outliers were excluded, leaving 46 observations. The article reports this selection transparently and does not treat outlier deletion as evidence of misconduct. Fraud risk is represented by the continuous Beneish M-Score. Managerial ownership is negatively associated with fraud risk (B=−7.627, p=0.012). Independent commissioners (B=1.511, p=0.085) and audit committee size (B=−0.196, p=0.519) are not significant. ROA does not moderate the three relationships. Structural compliance alone may not capture governance effectiveness, managerial ownership is the only tested mechanism associated with lower fraud risk. The study provides transparent Beneish M-Score evidence from Indonesian pharmaceutical companies and clarifies the inferential limits created by a small, sector-specific sample.